IMPLEMENTATION OF MANDATORY ENTERPRISE REGISTRATION (WDP) FOLLOWING THE EFFECTIVENESS OF LAW NO. 40 YEAR 2007 CONCERNING LIMITED LIABILITY COMPANIES IN THE ERA OF REGIONAL AUTONOMY - Hertanto, Ari Wahyudi (UI Scholars Hub, 2014)
Implementation of company registration shall be constrained because of differences in the interpretation of the meaning of the provisions of Article 29 of Law No. 40 of 2007 on Limited Liability Company, which determines that the registration of the company held by the Ministry of Justice and Human Rights. The provisions of Article 29 is interpreted by many practitioners as lex specialis of Act 3 of 1982 regarding Company Registration Requirement. The reality is not so. Company registration remains to be done pursuant to Act 3 of 1982. There are no provisions that override or cancel that Act 3 of 1982 to enforce Article 29 of Law No. 40 of 2007. Each law urgency is equally important. Act 40 of 2007 for the purpose of publication, while Act 3 of 1982 is to find out information about the company, either types of business activities, locations, shares and so forth. Registration of the company is still to be done on both the ministry under the provisions of law referred to.